Somatic stimulation causes frontoparietal cortical changes in neonates: a functional near-infrared spectroscopy study - Kashou, Nasser H. (Neurophotonics, 2016)
Palmar and plantar grasp are the foremost primitive neonatal reflexes and functions. Persistence of these reflexes in infancy is a sign of evolving cerebral palsy. Our aims were to establish measurement feasibility in a clinical setting and to characterize changes in oxyhemoglobin (HbO) and deoxyhemoglobin (HbD) concentration in the bilateral frontoparietal cortex in unsedated neonates at the crib-side using functional near-infrared spectroscopy (fNIRS). We hypothesized that bilateral concentration changes will occur upon somatic central and peripheral somatic stimulation. Thirteen preterm neonates (five males) underwent time 1, and six (two males) returned for time 2 (mean [Formula: see text] and 47.0 weeks, respectively). Signals from a total of 162 somatic stimuli responses were measured. Response amplitude, duration, and latency were log-transformed and compared between palmar, plantar, and oromotor stimuli using linear mixed models, adjusted for cap, electroencephalogram abnormality, time (1 versus 2), and Sarnat score, if necessary. The oromotor stimulus resulted in a 50% greater response than the palmar or plantar stimuli for HbO left and right hemisphere duration ([Formula: see text]). There were no other statistically significant differences between stimuli for any other outcome ([Formula: see text]). Utilizing fNIRS in conjunction with occupational and physical therapy maneuvers is efficacious to study modifiable and restorative neurophysiological mechanisms.